The Efficiency of Working Capital Use at Vietnam Payment Solution Joint Stock Company - Giang, Luong Hoang; Co, Nguyen Trong (Business and Economic Research, 2024)
Artificial intelligence changes production and has significant impacts on businesses. Besides great opportunities, this revolution will create a number of challenges, affecting the operations of the business community in general and Vietnam payment solution Joint Stock Company in particular. Through the research on the current situation of working capital use at Vietnam payment solution joint stock company, the author proposes recommendations to ensure sufficient cash reserves for the business’s payment needs and improve the efficiency of working capital use at the company.